Education in the United Arab Emirates 2019
DOI: 10.1007/978-981-13-7736-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Language Education in the UAE: Choosing the Right Drivers

Abstract: This chapter describes the many initiatives that have been spearheaded by the United Arab Emirates (UAE) in an effort to develop the teaching and learning of Arabic in the country. Although there has been unprecedented attention given to Arabic language education in the decade up to 2018, including an Arabic language charter, a reading law, the Arabic reading challenge, the Arabic for life report, and the Arabic award to list just a few, private and public schools are still having some challenges in bringing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…The various dialects exist mostly in spoken form and are not always mutually intelligible. They are used in day‐to‐day interactions between Arabic speakers (Thomure, 2019).…”
Section: Self‐regulation the Multilingual Teacher And Arabicmentioning
confidence: 99%
See 2 more Smart Citations
“…The various dialects exist mostly in spoken form and are not always mutually intelligible. They are used in day‐to‐day interactions between Arabic speakers (Thomure, 2019).…”
Section: Self‐regulation the Multilingual Teacher And Arabicmentioning
confidence: 99%
“…The effects of such changes can be witnessed in recent studies, which indicates that Emirati students are more strongly motivated to learn English than they are other foreign languages, whereas expat students are generally less motivated to learn Arabic than they are English and other foreign languages (Calafato & Tang, 2019a, 2019b). This is despite the UAE government's efforts to promote the learning and use of Arabic through numerous initiatives and directives (for an overview, see Thomure, 2019). According to some researchers (e.g., Thomure, 2019), this simultaneous prioritizing of English and lower motivation to learn Arabic could be occurring because private schools do not give Arabic enough importance, oftentimes because the generally Western expat leadership in such schools is neither proficient in Arabic nor do they have much background knowledge about it.…”
Section: Self‐regulation the Multilingual Teacher And Arabicmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies use various theoretical frameworks to achieve the objectives of the research. Several studies (Imenda, 2014;Haron et al, 2016;Taha, 2019;Carroll et al, 2017;Harrison, 2018;Alkutich, 2017;Cook, 2016;O'Neill, 2017;Ahmad, 2018) used the interpretivism theoretical models. Interpretivism involves a fundamental research approach in sociology that integrates human interest in the study.…”
Section: Synthesis Of Key Concepts and Theoretical Conceptsmentioning
confidence: 99%
“…Additionally, Belhiah and Elhami (2015) found that English was rapidly becoming a priority language in instruction in most schools in Dubai and other major UAE cities. Taha (2019) and attributed the trend to the increasing immigrant population in the UAE. Besides, Belhiah and Elhami (2015) reveal that convolutions and debates exist about the universality of using the Arabic language for decisions in pedagogical institutions.…”
Section: Synthesis Of Main Empirical Finding and Practical Implicationsmentioning
confidence: 99%